Sacrilege versus civility Muslim perspectives on the Satanic Verses affair - Ahsan, M.M; Kidwai, A.R (Islamic Foundation, 1991)
Apart from studying the Satanic Verses Affair from the Muslim perspective, relates it to the broader context of the conflict between faith and godlessness in our times. Covering the whole range of the Affair -- the largely unacknowledged peaceful Muslim protest, the widely reported symbolic book-burning in Bradford, the fatwa and the latest twist -- Rushdie's 'conversion' to Islam, it states the Muslim belief in the primacy of civility over sacrilege.